1997
DOI: 10.1007/3-540-63931-4_278
|View full text |Cite
|
Sign up to set email alerts
|

Skin-color modeling and adaptation

Abstract: Abstract. This paper studies a statistical skin-color model and its adaptation. It is revealed that 1 human skin colors cluster in a small region in a color space; 2 the variance of a skin color cluster can be reduced by i n tensity normalization, and 3 under a certain lighting condition, a skin-color distribution can be characterized by a m ultivariate normal distribution in the normalized color space. We then propose an adaptive model to characterize human skin-color distributions for tracking human faces un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(77 citation statements)
references
References 7 publications
0
77
0
Order By: Relevance
“…Statistical approaches can be subdivided further into: parametric approaches [4,5,7,8,12,22,24,25] and non-parametric approaches [1,14,20,31].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical approaches can be subdivided further into: parametric approaches [4,5,7,8,12,22,24,25] and non-parametric approaches [1,14,20,31].…”
Section: Related Workmentioning
confidence: 99%
“…A number of different color spaces have been used; however, normalized RGB [7,12,20,31] and HSV [8,14,22,24] are the most common color spaces used. It has been shown that in addition to being tolerant to minor variations in the illuminant, these color spaces also tend to produce minimum overlap between skin-color and background-color distributions [23].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…While invariant to most movements, colours are highly susceptible to lighting conditions; shadows, sensor errors, light colour temperature and directionality of the light source, all contribute in the way colours are represented [32]. Yang et ah [33] have observed that despite environmental conditions, skin colours have a tendency to cluster within the RGB colour space. Specifically the clustering effect can be modeled using a Gaussian distribution (see Figure 2.2).…”
Section: Methodsmentioning
confidence: 99%
“…This colour property is said to follow Gaussian statistics [33]. By constructing an appropriate statistical model and applying a threshold to each pixel's membership to this model, identification of skin patches can be made.…”
Section: Probabilistic Skin Filtersmentioning
confidence: 99%